Effect of 5[alpha]-reductase inhibitors on LNCaP cells, Syrian hamster flank organs, and TRAMP mice prostate cancer - Opoku-Acheampong, Alexander Boadu (Kansas State University, 2015)
The growth-inhibitory effect of saw palmetto supplements (SPS) with high long-chain fatty acids (FA)-low phytosterols (HLLP), high long-chain FA-high phytosterols (HLHP), and high medium-chain FA-low phytosterols (HMLP) was determined using androgen-sensitive LNCaP prostate cancer (PCa) cells and Syrian hamster flank organs. In vitro, all three SPS at high concentrations significantly decreased dihydrotestosterone-stimulated LNCaP cell number. HMLP and HLLP at high concentrations significantly decreased, but HLHP which significantly increased testosterone-stimulated LNCaP cell number. In Syrian hamsters, all three SPS treatments caused notable, but nonsignificant reduction in the difference between the left and right flank organ growth in the testosterone-, but not dihydrotestosterone-treated SPS groups. Results suggest SPS might be a mild 5-alpha-reductase (5-alpha-R) inhibitor. The pharmaceuticals finasteride inhibits 5-alpha-R2, and dutasteride inhibits 5-alpha-R1 and 5-alpha-R2 isoenzymes. Because finasteride inhibits only 5-alpha-R2, we hypothesized that it would not be as efficacious in preventing PCa development and/or progression in TRAMP mice as dutasteride. Six-week-old C57BL/6 TRAMP x FVB male mice were randomized to control, pre- and post- finasteride and dutasteride diet groups that began at 6 and 12 weeks of age, respectively, and terminated at 20 weeks of age. Pre and post groups received drugs before and after mice were expected to develop PCa, respectively. Post-Dutasteride treatment was significantly more effective than Pre-Dutasteride; and dutasteride treatments significantly more effective than finasteride treatments in decreasing prostatic intraepithelial neoplasia progression and PCa development. The finasteride groups and the Pre-Dutasteride group had significantly increased incidence of poorly differentiated PCa versus control. Androgen receptor and Ki-67 protein, DNA fragmentation from apoptosis, 5-alpha-R1 and 5-alpha-R2 mRNA levels were determined in mice with genitourinary weight less than 1 gram and greater than 1 gram to elucidate the discordant response in Pre-Dutasteride and finasteride groups, and Post-Dutasteride’s efficacy. Results suggest the difference in genitourinary weights is influenced more by proliferation, rather than androgen receptor and apoptosis in tumor. Mice age may not be significantly important in regulating proliferation, androgen receptor and apoptosis to promote tumor growth. In conclusion, the results with 5-alpha-reductase inhibitors may support the therapeutic use of dutasteride, but not finasteride, or saw palmetto supplements.
Keywords: Prostate cancer; 5-alpha-reductase; finasteride; dutasteride; saw palmetto; benign prostatic hyperplasia; Biology (0306); Nutrition (0570); Oncology (0992)